HUBUNGAN PENGETAHUAN TERHADAP TINDAKAN DALAM PEMILIHAN SAMPAH DI SD MUHAMMADIYAH 3 KOTA PADANGSIDIMPUAN - Nasution, Nurul Hidayah; Siregar, Yuli Arisyah; Jufri, Soleman; Harahap, Dewani; Batubara, Adli Zil Ikrom; Mapilinda, Via Nesa; Harahap, Rosmawarni (Universitas Aufa Royhan, 2025)
Waste is an inseparable element of human life, and its volume tends to increase along with population growth and urbanization. waste has a significant impact on health including aesthetic problems, being a hotbed of disease vectors, a source of infection and a cause of water and soil pollution. The purpose of the study was to determine the relationship between knowledge and action in the selection of waste at SD Muhammadiyah 3 Padangsidimpuan City. The type of research is quantitative research. The research design is cross sectional. The research location was at SD Muhammadiyah 3 Padangsidimpuan City. The study population was elementary school students who were in grade 5. The study sample was 30 students. The sample was selected by total sampling technique. The research used a questionnaire. Data processing starts from the stages of data editing (checking data), data entry (entering data), and tabulating data (compiling data). Data were analyzed using univariate and bivariate tests. The results showed that the relationship between knowledge and action in the selection of waste at SD Muhammadiyah 3 Padangsidimpuan City with a p-value (0.022 <0.05). It is suggested to the school, that there is a need for support from the school environment community such as: principals, teachers, school guards and canteen guards in supporting the waste management program by holding routine activities, such as community service in cleaning the classroom, making handicrafts from items that are no longer used.